UV adhesive composition, UV anti-viscosity adhesive and UV anti-viscosity film
By using specific UV adhesive compositions in UV mucosa and combining the mutual cooperation of non-photosensitive resins and photosensitive resins, the problem of overflow and low process yield in flexible or curved material treatment is solved, and efficient bonding is achieved and crosslinking improve process quality.
Patent Information
- Application Number
- CN202111675802.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The existing UV mucosa reduces the membranes have problems with spilling and low process yields in flexible or curved material treatments.
A UV viscose composition is adopted, including 38 to 80 wt% of mixed resin, 10 to 48 wt% of active monomer, 0.01 to 5 wt% of photoinitiator, 0.01 to 5 wt% of curing agent, and 0.01 to 40 wt% of solvent , through the cooperation of the non-photosensitive resin and the photosensitive resin, thermal curing and photocuring are achieved, achieving suitable viscosity and cross-linking density.
It effectively reduces the chance of glue spills, reduces the difficulty of peeling in the process, improves the process yield, and maintains high adhesion and acid-base resistance during flexible or curved material treatment.
Smart Images

Figure BDA0003451247570000081 
Figure BDA0003451247570000091 
Figure BDA0003451247570000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of UV anti-viscosity films, and in particular to a UV adhesive composition, a UV anti-viscosity adhesive and a UV anti-viscosity film. Background Art
[0002] When cutting and grinding optical glass and semiconductor materials during processing, a special protective film is needed to bond and fix them. After processing, the processed materials can be easily peeled off from the fixed film without affecting the material itself. UV anti-adhesive film is also known as UV adhesive tape, UV anti-adhesive tape, UV adhesive tape, UV anti-adhesive temporary bonding film. UV anti-adhesive film is a single-sided tape made of a special glue that is coated on a special film and shows high adhesion (2000gf / 25mm for SUS) in normal conditions, but the adhesion drops sharply after ultraviolet irradiation (10gf / 25mm for SUS).
[0003] UV anti-adhesive film has high adhesion when used for cutting, and can ensure that the material does not scatter, leave residual glue, prevent damage, and expand during cutting, grinding, and other processing. The UV irradiation reaction time is fast, ensuring the quality during the processing and effectively improving work efficiency. There is no residual glue or breakage when peeling off, ensuring the subsequent process, and it is anti-static and acid-alkali resistant.
[0004] However, on flexible panels or many shapes with large angles, irregularities or even curved surfaces, a UV anti-adhesion film with greater adhesion is needed to fix it, so as to avoid weak adhesion due to too little adhesion, which affects the process. Therefore, it is not enough to be widely used in the manufacturing process of flexible or curved AMOLED displays. At present, the adhesion of UV anti-adhesion film is not strong (<2000gf / 25mm for SUS) and static electricity is generated during use, which is easy to damage the processed materials and easy to fall off during the process. At the same time, there is also the problem of overflowing glue, that is, as the bonding strength increases, the UV anti-adhesion film still has overflowing glue, and the overflowing glue is easy to adhere to the flexible panel, thereby affecting the process yield. Summary of the invention
[0005] The main purpose of the present invention is to provide a UV adhesive composition, a UV viscosity-reducing adhesive and a UV viscosity-reducing film, so as to solve the problems of UV viscosity-reducing films in the prior art such as adhesive overflow and low process yield.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a UV adhesive composition is provided, which comprises, by mass percentage, 38-80wt% of a mixed resin, 10-48wt% of an active monomer, 0.01-5wt% of a photoinitiator, 0.01-5wt% of a curing agent, and 0.01-40wt% of a solvent; wherein the mixed resin is a non-photosensitive resin and a photosensitive resin, the non-photosensitive resin is selected from any one or more of an epoxy resin, a hydroxyl-containing resin, and a polyurethane resin, and the photosensitive resin is a difunctional acrylic resin and / or a multifunctional acrylic resin.
[0007] Furthermore, the content of the non-photosensitive resin is 35-50 wt %, and preferably the mass ratio of the non-photosensitive resin to the photosensitive resin is 0.8-1.6:1.
[0008] Furthermore, the mass ratio of the above-mentioned epoxy resin, hydroxyl-containing resin and polyurethane resin is 1:0.4~4:0.4~4, preferably the weight average molecular weight Mw of the epoxy resin is 5000~60000, preferably the epoxy resin is selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol epoxy resin, bisphenol F epoxy resin; and / or the weight average molecular weight Mw of the hydroxyl-containing resin is 3000~60000, preferably the hydroxyl-containing resin is selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, diepoxy glycol bisglycidyl ether resin; and / or the weight average molecular weight Mw of the polyurethane resin is 5000~100000, preferably the polyurethane resin is selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin, polyester polyurethane resin.
[0009] Further, the weight average molecular weight Mw of the above-mentioned photosensitive resin is 3000-100000, preferably 5000-50000, the difunctional acrylic resin is preferably selected from any one or more of bisphenol A epoxy acrylic resin, polyurethane acrylic resin, and polyester acrylic resin, and the content of the difunctional acrylic resin is preferably 10-40wt%, and the multifunctional acrylic resin is preferably selected from any one or more of graft-modified acrylic resin, phenolic epoxy acrylic resin, and polyurethane acrylic resin. The graft-modified acrylic resin is an acrylic resin with a side chain grafted with a (meth) acrylic monomer, and the (meth) acrylic monomer is preferably selected from any one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl acrylate. The content of the multifunctional photosensitive resin is preferably 10-30wt%, and further, the mass ratio of the difunctional acrylic resin to the multifunctional acrylic resin is preferably 1-4:1.
[0010] Furthermore, the mass ratio of the above-mentioned mixed resin to the active monomer is 1:0.5-4, and the active monomer is preferably a photosensitive monomer and / or a non-photosensitive monomer, the content of the photosensitive monomer is ≤40wt%, and the content of the non-photosensitive monomer is ≥30wt%. The photosensitive monomer preferably includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer, and the mass of the difunctional monomer and / or the multifunctional monomer is denoted as m, and the ratio of the mass of the monofunctional monomer to m is preferably 1:1-5; the non-photosensitive monomer includes any one or more of a hydroxyl-containing monomer and an epoxy group monomer.
[0011] Furthermore, the content of the above-mentioned photoinitiator is 0.05-3wt%, and the photoinitiator is preferably a free radical photoinitiator, and the free radical photoinitiator is preferably selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
[0012] Furthermore, the content of the above-mentioned curing agent is 0.5-2wt%, and the curing agent preferably includes an isocyanate curing agent, and the isocyanate curing agent is preferably selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate. The curing agent also preferably includes an amine curing agent, and the mass ratio of the isocyanate curing agent to the amine curing agent is preferably 1:0.01-0.4, and the amine curing agent is preferably selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, and polyethylenepolyamine.
[0013] Furthermore, the UV adhesive composition further comprises 0.01 to 5 wt % of an antistatic agent, preferably 0.05 to 3 %, wherein the antistatic agent is preferably selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonyl imide), tributylmethylammonium bis(trifluoromethanesulfonyl imide salt, and nanometal wires.
[0014] Furthermore, the content of the above-mentioned solvent is 10-30wt%, and the solvent is preferably selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether, and toluene.
[0015] According to another aspect of the present invention, a UV viscosity-reducing adhesive is provided, which is prepared by mixing various components of an adhesive composition, and the adhesive composition is the aforementioned UV adhesive composition.
[0016] According to another aspect of the present invention, a UV anti-viscosity film is provided, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, wherein the UV anti-viscosity adhesive is the above-mentioned UV anti-viscosity adhesive.
[0017] By applying the technical solution of the present invention, the present application achieves the appropriate viscosity of the adherend through the mutual cooperation of non-photosensitive resin and photosensitive resin, through thermal curing and light curing. When UV irradiation with appropriate energy is provided, the photoinitiator absorbs the radiation energy, and produces free radicals with initiator polymerization ability through chemical changes, and then cross-links and cures with the photosensitive resin, so that the UV glue loses its bonding ability, that is, the effect of reducing viscosity is achieved. And the UV viscosity-reducing glue obtained by the cooperation with the other components has a suitable cross-linking density, hardness and viscosity, which helps to reduce the probability of overflow glue, reduce the difficulty of peeling in the process, and improve the process yield. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As analyzed in the background technology, the UV anti-viscosity film in the prior art has problems of adhesive overflow and low process yield. To solve this problem, the present invention provides a UV adhesive composition, a UV anti-viscosity adhesive and a UV anti-viscosity film.
[0020] In a typical embodiment of the present application, a UV adhesive composition is provided, which comprises, by mass percentage: 38 to 80 wt % of a mixed resin, 10 to 48 wt % of an active monomer, 0.01 to 5 wt % of a photoinitiator, 0.01 to 5 wt % of a curing agent, and 0.01 to 40 wt % of a solvent; wherein the mixed resin is a non-photosensitive resin and a photosensitive resin, the non-photosensitive resin is selected from any one or more of an epoxy resin, a hydroxyl-containing resin, and a polyurethane resin, and the photosensitive resin is a difunctional acrylic resin and / or a multifunctional acrylic resin.
[0021] The present application achieves the appropriate viscosity of the adherend through the mutual cooperation of non-photosensitive resin and photosensitive resin, through heat curing and light curing. When UV irradiation with appropriate energy is provided, the photoinitiator absorbs the radiation energy, and after chemical changes, produces free radicals with initiator polymerization ability, which then cross-link and cure with the photosensitive resin, causing the UV glue to lose its bonding ability, that is, achieving the effect of reducing viscosity. The UV viscosity-reducing glue obtained by the cooperation with the other components has an appropriate cross-linking density, hardness and viscosity, which helps to reduce the probability of glue overflow, reduce the difficulty of peeling in the process, and improve the process yield.
[0022] The combination of the non-photosensitive resin and the photosensitive resin can achieve the synergistic effect of the functional groups in the two types of resins, thereby obtaining a UV adhesive composition with better performance.
[0023] In order to further improve the synergistic effect between the non-photosensitive resin and the photosensitive resin, the content of the non-photosensitive resin is preferably 35-50wt%, and the mass ratio of the non-photosensitive resin to the photosensitive resin is preferably 0.8-1.6:1.
[0024] Epoxy resin can increase the cross-linking density and improve the glass transition temperature Tg. Hydroxyl-containing resin has high adhesion and good flexibility, helps to improve viscosity and control coating properties. Polyurethane resin has high strength, helps to improve bonding strength and has excellent weather resistance. The preferred mass ratio of epoxy resin, hydroxyl-containing resin and polyurethane resin is 1:0.1-4:0.1-4, which helps to maximize the synergistic effect between the three.
[0025] In some embodiments of the present application, the weight average molecular weight Mw of the epoxy resin is 5000-60000, such as the weight average molecular weight Mw of the epoxy resin is 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, etc., and the epoxy resin is preferably selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol epoxy resin, and bisphenol F epoxy resin;
[0026] In some embodiments of the present application, the weight average molecular weight Mw of the hydroxyl-containing resin is 3000-60000, such as the weight average molecular weight Mw of the hydroxyl-containing resin is 3000, 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, etc., preferably, the hydroxyl-containing resin is selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, and diepoxy ethylene glycol diglycidyl ether resin;
[0027] In some embodiments of the present application, the weight average molecular weight Mw of the polyurethane resin is 5000-100000, such as the weight average molecular weight Mw of the polyurethane resin is 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, 70000, 80000, 90000, 100000, etc., and the polyurethane resin is preferably selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin, and polyester polyurethane resin. Among them, the smaller the side chain group in the above polyester polyurethane resin and polyether polyurethane resin, the more methylene groups between ether bonds or ester bonds, and the higher the molecular weight of the crystalline soft segment, so that the polyurethane resin has higher crystallinity and greater bonding strength.
[0028] In some embodiments of the present application, the weight average molecular weight Mw of the photosensitive resin is 3000-100000, preferably 5000-50000, such as the weight average molecular weight Mw of the photosensitive resin is 3000, 5000, 10000, 30000, 50000, 80000, 100000, etc., preferably 5000, 10000, 30000, 50000, etc., preferably the bifunctional acrylic resin is selected from any one or more of bisphenol A epoxy acrylic resin, polyurethane acrylic resin, polyester acrylic resin, and the content of the bifunctional acrylic resin is preferably The content of the multifunctional photosensitive resin is preferably 10 to 40 wt %, and the multifunctional acrylic resin is preferably selected from any one or more of a graft modified acrylic resin, a phenolic epoxy acrylic resin, and a polyurethane acrylic resin. The graft modified acrylic resin is an acrylic resin having a (meth) acrylic monomer grafted on the side chain. The (meth) acrylic monomer is preferably selected from any one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl acrylate. The content of the multifunctional photosensitive resin is preferably 10 to 30 wt %. Furthermore, the mass ratio of the difunctional acrylic resin to the multifunctional acrylic resin is preferably 1 to 4:1.
[0029] The functional groups between the preferred bifunctional acrylic resin and the multifunctional acrylic resin can be better coordinated and matched with the active monomer and other components in the UV adhesive composition, so as to give full play to the advantages of the photosensitive resin. In combination with the preferred non-photosensitive resin, it is more helpful to control the viscosity of the UV adhesive and balance the adhesion, crosslinking density, flexibility, hardness and strength of the UV adhesive, so that it can be easily prepared and coated, thereby helping to reduce the probability of overflow, reduce the difficulty of peeling in the process, and improve the process yield; and make the adhesive composition have excellent heat resistance, further meeting the use of the flexible panel process.
[0030] Photosensitive monomers are active monomers that mainly dissolve and dilute oligomers, adjust the viscosity of the system, and most importantly, participate in the photocuring reaction. If the content is too low, there will be insufficient crosslinking, and there will be problems with low curing speed and adhesion. Adding too much can easily reduce the viscosity of the UV anti-viscosity adhesive, affecting the coating, the photocuring speed is fast, the crosslinking density after curing is large, the hardness of the reaction adhesive layer after curing is high, and the brittleness is large, which is not conducive to improving the bonding strength, thereby limiting its application in the process of flexible or curved components. Therefore, it is preferred that the photosensitive monomer is matched with a non-photosensitive monomer, mainly to increase the molecular weight and improve the adhesion, thereby helping to improve the bonding strength of the UV anti-viscosity adhesive and expand its application in the process of flexible or curved components. Preferably, the mass ratio of the above-mentioned mixed resin to the active monomer is 1:0.5-4, and the active monomer is preferably a photosensitive monomer and / or a non-photosensitive monomer, the content of the photosensitive monomer is ≤40wt%, and the content of the non-photosensitive monomer is ≥30wt%, which is more conducive to the synergistic effect between the mixed resin and the active monomer, the photosensitive monomer and the non-photosensitive monomer, thereby improving the performance of the UV anti-viscosity adhesive.
[0031] Preferably, the photosensitive monomer includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer.
[0032] In combination with the synergistic combination effect of the mixed resin or photosensitive monomer structure, the monofunctional monomer is preferably selected from any one or more of hydroxyethyl methacrylate, ethoxyethyl acrylate, ethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, diisooctyl maleate, and monomers containing functional groups. The monomer containing functional groups is preferably selected from any one or more of ethoxylated neopentyl glycol methoxy monoacrylate, 1,6-hexanediol methoxy monoacrylate, ethoxyethoxyethyl acrylate, and methoxyethyl acrylate, and is further preferably a combination of hydroxyethyl methacrylate and methyl methacrylate. In order to further improve the synergistic effect of the difunctional monomer and the multifunctional monomer with the monofunctional monomer, the difunctional monomer is preferably selected from any one or more of tripropylene glycol diacrylate, dipropylene glycol diacrylate, hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol divinyl ether, and ethoxylated bisphenol A epoxy acrylate, and the multifunctional monomer is preferably selected from any one or more of trimethylolpropane triacrylate, pentaerythritol triacrylate, ditrihydroxymethylpropane tetraacrylate, and dipentaerythritol penta / hexaacrylate, and further preferably one or a combination of two of dipentaerythritol penta / hexaacrylate.
[0033] The mass of the bifunctional monomer and / or multifunctional monomer is recorded as m. If the amount of monofunctional monomer added is too much, the adhesive layer will be soft after curing, and if the amount added is too little, the adhesive layer will be too hard after curing. Therefore, the content of monofunctional monomer in the photosensitive monomer is preferably 20-40wt%. If too much bifunctional and multifunctional monomers are added, the reaction adhesive layer will be hard after curing, which is not conducive to improving the bonding strength and limiting its application in the process of flexible or curved components. Therefore, the ratio of the mass of monofunctional monomer to m is preferably 1:1-5; non-photosensitive monomers include any one or more of monomers containing hydroxyl groups and epoxy group monomers. Further, it is preferred that the non-photosensitive monomer is selected from any one or more of diepoxy ethylene glycol diglycidyl ether, polyester diol, polyether diol, and alkyl diol, so as to take into account the peel strength of the UV viscosity-reducing film before and after UV irradiation.
[0034] After being irradiated by ultraviolet light, the photoinitiator absorbs the energy of light and splits into multiple active free radicals, which trigger a chain polymerization reaction between the photosensitive resin and the active monomer, causing the UV viscosity-reducing adhesive to crosslink and solidify. If too much photoinitiator is added, the coating surface will absorb too much ultraviolet light to initiate, which will weaken the penetration of ultraviolet light, resulting in incomplete curing of the bottom layer. There will be problems such as excessive peel strength of the UV viscosity-reducing film after UV irradiation, residual glue and storage thermal stability, which is not conducive to improving the process yield; when the amount of photoinitiator added is too little, it is not conducive to the complete reaction of the photosensitive resin and the active monomer, and it is still easy to cause excessive peel strength of the UV viscosity-reducing film after UV irradiation, and residual glue, which is not conducive to improving the process yield. Therefore, the content of the above-mentioned photoinitiator is preferably 0.05-3wt%, such as the preferred photoinitiator content of the present application is 0.5wt%, 1wt%, 1.5wt%, 2wt%, 3wt%, etc. The preferred photoinitiator is a free radical photoinitiator, and the preferred free radical photoinitiator is selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
[0035] Adding too much curing agent will cause the non-photosensitive resin to react completely, which is not conducive to reducing the peel strength before UV irradiation. Adding too little will cause the non-photosensitive resin to react too little, resulting in excessive peel strength, and at the same time make the peel strength after UV irradiation too large and there will be residual glue problems. In order to take into account the peel strength before and after UV irradiation, the content of the above-mentioned curing agent is preferably 0.5-2wt%. For example, the preferred curing agent content of the present application is 0.5wt%, 0.51wt%, 1wt%, 1.5wt%, 2wt%, etc.
[0036] The content of the curing agent is 0.5-2wt%, and the curing agent preferably includes an isocyanate curing agent, and the isocyanate curing agent is preferably selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate. Further, the isocyanate curing agent is preferably selected from any one or more of Coronate LS, 2037, Desmodur L-75, Takenate D-101E, and Risheng SC-75LT. The isocyanate curing agent contains a highly unsaturated structure of isocyanate group (-NCO), which determines that it has a higher reactivity. The curing agent reacts with the epoxy group in the epoxy resin to generate a hydroxyl group, and the hydroxyl group reacts with the isocyanate again, and at the same time includes the reaction between the isocyanate and the polyol and its small molecule alcohol, so as to be more conducive to exerting its curing performance.
[0037] In some embodiments, the curing agent preferably further comprises an amine curing agent, and the mass ratio of the isocyanate curing agent to the amine curing agent is preferably 1:0.01-0.4, and the amine curing agent is preferably selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, and polyethylenepolyamine. Among them, the isocyanate curing agent is used in combination with the amine curing agent, and the amine ions in the amine curing agent can also react with the epoxy group and isocyanate in the epoxy resin to produce OH groups, thereby reacting with other resins or isocyanate curing agents, thereby improving the curing efficiency of the mixed resin.
[0038] In order to reduce the influence of static electricity on the workpiece and improve the process yield, the above-mentioned UV adhesive composition preferably also includes 0.01-5wt% of an antistatic agent, such as the content of the preferred antistatic agent in the present application is 0.01wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.9wt%, 5wt%, etc., preferably 0.05-3%, such as the content of the preferred antistatic agent in the present application is 0.05wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc., and the antistatic agent is preferably selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonyl imide), tributylmethylammonium bis(trifluoromethanesulfonyl imide salt, and nanometal wires.
[0039] In one embodiment of the present application, the content of the above-mentioned solvent is 10-30wt%, and the preferred solvent is selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether, and toluene.
[0040] The solvent can adjust the viscosity of the adhesive composition, so that the difficulty of coating will not be increased due to excessive viscosity, nor will it be impossible to coat a thicker adhesive layer due to too low viscosity, and at the same time, the baking time after coating will be long, thereby reducing the production efficiency. For example, the preferred solvent content in the present application is 0.1wt%, 1.88wt%, 5.5wt%, 10wt%, 15wt%, 17.49wt%, 18.09wt%, 18.49wt%, 20wt%, 22.45wt%, 25wt%, 27wt%, 30wt%, 35wt%, 40wt%, etc., and further, it is preferably 10wt%, 15wt%, 17.49wt%, 18.09wt%, 18.49wt%, 20wt%, 22.45wt%, 25wt%, 27wt%, 30wt%, etc.
[0041] In another typical embodiment of the present application, a UV viscosity-reducing adhesive is provided, which is prepared by mixing various components of an adhesive composition, and the adhesive composition is the aforementioned UV adhesive composition.
[0042] By controlling the content of each component in the UV adhesive composition within the above range and through the synergistic coordination of the remaining components, the UV viscosity-reducing adhesive has a suitable cross-linking density, hardness and viscosity, which helps to reduce the probability of glue overflow. And the UV viscosity-reducing film including the UV viscosity-reducing adhesive of the present application has high adhesion and acid and alkali resistance when used for cutting, and ensures that the material does not scatter, does not have residual glue, does not expand, and prevents damage during cutting, grinding and other processing. Even on flexible panels or many shapes with large angles, irregular or even curved surfaces, it protects, fixes and supports flexible or curved surfaces. The UV irradiation reaction time is fast, which ensures the quality during the processing and effectively improves work efficiency. There is no residual glue or broken glue when peeling, which reduces the peeling force in the process, improves the process yield, and ensures the subsequent process.
[0043] In another typical embodiment of the present application, a UV anti-viscosity film is provided, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, wherein the UV anti-viscosity adhesive is the above-mentioned UV anti-viscosity adhesive.
[0044] The UV anti-viscosity film including the above-mentioned UV anti-viscosity adhesive of the present application reduces the peeling force in the process, improves the process yield, and ensures the subsequent processes.
[0045] Among them, the preferred preparation method of the UV anti-viscosity film comprises: adding a mixed resin, an active monomer, an antistatic agent and a solvent into a reaction kettle and mechanically stirring at a uniform speed for 1 to 3 hours to obtain a main agent A.
[0046] Under yellow light or in dark, add photoinitiator to main agent A in proportion and stir mechanically for 15 to 60 minutes, then add curing agent and stir mechanically for 15 to 60 minutes to obtain antistatic UV anti-viscosity adhesive, wherein the addition ratio of each component refers to the corresponding ratio in the adhesive composition; finally, apply it on 50 μm thick PET, PO and PVC substrates by scraping or slit coating machine, put it into 80 to 110 ° C oven for 1 to 5 minutes after coating, and the thickness of the adhesive film after drying is about 10 to 30 μm, then use flat film laminating machine to attach release film, select PET light release film release surface to attach to the dried UV anti-viscosity adhesive, and finally obtain UV anti-viscosity film.
[0047] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0048] Example 1
[0049] The UV adhesive composition of Example 1 is shown in Table 1.
[0050] Among them, the specific mixed resins included are as follows:
[0051] Resin A1 (hydroxyl-containing resin): VORANOL 3003N;
[0052] Resin A2 (polyether polyurethane resin): Mw = 60000;
[0053] Resin A3 (bisphenol A type epoxy resin): E-20 (601);
[0054] Resin B1 (bifunctional acrylic resin): Changxing DR-U394;
[0055] Resin B2 (multifunctional acrylic resin): Changxing DR-U202.
[0056] Table 1
[0057]
[0058] Example 2
[0059] The difference between Example 2 and Example 1 is that:
[0060] The content of resin A1 was 16 wt %, and the content of butyl acetate was 21.69 wt %, to obtain a UV adhesive composition.
[0061] Example 3
[0062] The difference between Example 3 and Example 1 is that:
[0063] The content of resin A1 was 32 wt %, and the content of butyl acetate was 5.69 wt %, to obtain a UV adhesive composition.
[0064] Example 4
[0065] The difference between Example 4 and Example 1 is that,
[0066] The content of resin A1 was 36 wt %, and the content of butyl acetate was 1.69 wt %, to obtain a UV adhesive composition.
[0067] Example 5
[0068] The difference between Example 5 and Example 1 is that
[0069] The content of resin A1 was 12 wt %, and the content of butyl acetate was 25.69 wt %, to obtain a UV adhesive composition.
[0070] Example 6
[0071] The difference between Example 6 and Example 1 is that
[0072] The UV adhesive composition of Example 6 is shown in Table 2.
[0073] Table 2
[0074]
[0075] Example 7
[0076] The difference between Example 7 and Example 6 is that:
[0077] The content of resin A1 is 18 wt %, the content of resin A2 is 10 wt %, and the content of resin A3 is 12 wt %, to obtain a UV adhesive composition.
[0078] Example 8
[0079] The difference between Example 8 and Example 7 is that:
[0080] The content of resin A1 was 2.96 wt %, the content of resin A2 was 29.63 wt %, and the content of resin A3 was 7.41 wt %, to obtain a UV adhesive composition.
[0081] Example 9
[0082] The difference between Example 9 and Example 7 is that:
[0083] The content of resin A1 was 29.63 wt %, the content of resin A2 was 2.96 wt %, and the content of resin A3 was 7.41 wt %, to obtain a UV adhesive composition.
[0084] Example 10
[0085] The difference between Example 10 and Example 7 is that
[0086] The content of resin A1 was 26 wt %, the content of resin A2 was 2 wt %, and the content of resin A3 was 12 wt %, to obtain a UV adhesive composition.
[0087] Embodiment 11
[0088] The difference between Example 11 and Example 7 is that
[0089] The content of resin A1 was 22.02 wt %, the content of resin A2 was 12.19 wt %, and the content of resin A3 was 14.68 wt %, to obtain a UV adhesive composition.
[0090] Example 12
[0091] The difference between Example 12 and Example 1 is that
[0092] The content of resin B1 is 16 wt %, and the content of resin B2 is 4 wt %, to obtain a UV adhesive composition.
[0093] Example 13
[0094] The difference between Example 13 and Example 1 is that
[0095] The content of resin B1 is 15 wt %, and the content of resin B2 is 5 wt %, to obtain a UV adhesive composition.
[0096] Embodiment 14
[0097] The difference between Example 14 and Example 1 is that
[0098] The content of resin B1 was 6.7 wt %, and the content of resin B2 was 13.3 wt %, to obtain a UV adhesive composition.
[0099] Embodiment 15
[0100] The difference between Example 15 and Example 1 is that
[0101] The content of resin B1 was 16.7 wt %, and the content of resin B2 was 3.3 wt %, to obtain a UV adhesive composition.
[0102] Example 16
[0103] The difference between Example 16 and Example 1 is that
[0104] The content of resin A1 is 26wt%, the content of resin B1 is 13wt%, and the content of resin B2 is 13wt%;
[0105] The content of methyl methacrylate is 4.42 wt %, the content of dipropylene glycol diacrylate is 2.21 wt %, the content of ethoxylated bisphenol A epoxy acrylate is 2.21 wt %, and the content of diepoxy ethylene glycol bisglycidyl ether is 17.16 wt %, to obtain a UV adhesive composition.
[0106] Embodiment 17
[0107] The difference between Example 17 and Example 1 is that
[0108] The content of resin A1 is 7.8wt%, the content of resin B1 is 3.9wt%, and the content of resin B2 is 3.9wt%;
[0109] The content of methyl methacrylate is 10.61 wt %, the content of dipropylene glycol diacrylate is 5.30 wt %, the content of ethoxylated bisphenol A epoxy acrylate is 5.31 wt %, and the content of diepoxy ethylene glycol bisglycidyl ether is 41.18 wt %, to obtain a UV adhesive composition.
[0110] Embodiment 18
[0111] The difference between Example 18 and Example 1 is that
[0112] The content of resin A1 is 30wt%, the content of resin B1 is 15wt%, and the content of resin B2 is 15wt%;
[0113] The content of methyl methacrylate is 3.06wt%, the content of dipropylene glycol diacrylate is 1.53wt%, the content of ethoxylated bisphenol A epoxy acrylate is 1.53wt%, and the content of diepoxy ethylene glycol bisglycidyl ether is 11.88wt%, to obtain a UV adhesive composition.
[0114] Embodiment 19
[0115] The difference between Example 19 and Example 1 is that
[0116] The content of resin A1 is 6.5wt%, the content of resin B1 is 3.25wt%, and the content of resin B2 is 3.25wt%;
[0117] The content of methyl methacrylate is 11.05 wt %, the content of dipropylene glycol diacrylate is 5.52 wt %, the content of ethoxylated bisphenol A epoxy acrylate is 5.53 wt %, and the content of diepoxy ethylene glycol bisglycidyl ether is 42.9 wt %, to obtain a UV adhesive composition.
[0118] Embodiment 20
[0119] The difference between Example 20 and Example 1 is that
[0120] The content of methyl methacrylate is 3.25 wt %, the content of dipropylene glycol diacrylate is 4.87 wt %, and the content of ethoxylated bisphenol A epoxy acrylate is 4.88 wt %, to obtain a UV adhesive composition.
[0121] Embodiment 21
[0122] The difference between Example 21 and Example 1 is that
[0123] The content of methyl methacrylate is 2.17 wt %, the content of dipropylene glycol diacrylate is 5.41 wt %, and the content of ethoxylated bisphenol A epoxy acrylate is 5.42 wt %, to obtain a UV adhesive composition.
[0124] Embodiment 22
[0125] The difference between Example 22 and Example 1 is that
[0126] The content of methyl methacrylate is 8.67 wt %, the content of dipropylene glycol diacrylate is 2.16 wt %, and the content of ethoxylated bisphenol A epoxy acrylate is 2.17 wt %, to obtain a UV adhesive composition.
[0127] Embodiment 23
[0128] The difference between Example 23 and Example 1 is that
[0129] The content of methyl methacrylate is 1.86 wt %, the content of dipropylene glycol diacrylate is 5.57 wt %, and the content of ethoxylated bisphenol A epoxy acrylate is 5.57 wt %, to obtain a UV adhesive composition.
[0130] Embodiment 24
[0131] The content of resin A1 is 20wt%, the content of resin B1 is 10wt%, and the content of resin B2 is 8wt%;
[0132] The content of methyl methacrylate is 8wt%, the content of dipropylene glycol diacrylate is 8wt%, the content of ethoxylated bisphenol A epoxy acrylate is 8wt%, and the content of diepoxy ethylene glycol bisglycidyl ether is 24wt%;
[0133] The content of butyl acetate is 6wt%;
[0134] The content of lithium bis(trifluoromethanesulfonyl)imide LiTFSI is 3wt%;
[0135] The content of benzil dimethyl ether (651) is 3 wt%;
[0136] The content of toluene diisocyanate is 1.9 wt %; the content of diethylenetriamine is 0.1 wt %, and a UV adhesive composition is obtained.
[0137] Embodiment 25
[0138] The content of resin A1 is 30wt%, the content of resin B1 is 15wt%, and the content of resin B2 is 15wt%;
[0139] The content of methyl methacrylate is 2wt%, the content of dipropylene glycol diacrylate is 3wt%, the content of ethoxylated bisphenol A epoxy acrylate is 5wt%, and the content of diepoxy ethylene glycol bisglycidyl ether is 10wt%;
[0140] The content of butyl acetate is 5wt%;
[0141] The content of lithium bis(trifluoromethanesulfonyl)imide LiTFSI is 5wt%;
[0142] The content of benzil dimethyl ether (651) is 5wt%;
[0143] The content of toluene diisocyanate is 4.8 wt %; the content of diethylenetriamine is 0.2 wt %, and a UV adhesive composition is obtained.
[0144] Embodiment 26
[0145] The content of resin A1 is 40wt%, the content of resin B1 is 20wt%, and the content of resin B2 is 20wt%;
[0146] The content of methyl methacrylate is 1wt%, the content of dipropylene glycol diacrylate is 2wt%, the content of ethoxylated bisphenol A epoxy acrylate is 2wt%, and the content of diepoxy ethylene glycol diglycidyl ether is 5wt%;
[0147] The content of butyl acetate is 9.4wt%;
[0148] The content of lithium bis(trifluoromethanesulfonyl)imide LiTFSI is 0.05wt%;
[0149] The content of benzil dimethyl ether (651) is 0.05wt%;
[0150] The content of toluene diisocyanate is 0.48 wt %; the content of diethylenetriamine is 0.02 wt %, and a UV adhesive composition is obtained.
[0151] Embodiment 27
[0152] The content of resin A1 is 9.7wt%, the content of resin B1 is 5wt%, and the content of resin B2 is 5wt%;
[0153] The content of methyl methacrylate is 10wt%, the content of dipropylene glycol diacrylate is 6wt%, the content of ethoxylated bisphenol A epoxy acrylate is 4wt%, and the content of diepoxy ethylene glycol bisglycidyl ether is 20wt%;
[0154] The content of butyl acetate is 40wt%;
[0155] The content of lithium bis(trifluoromethanesulfonyl)imide LiTFSI is 0.01wt%;
[0156] The content of benzil dimethyl ether (651) is 0.01wt%;
[0157] The content of toluene diisocyanate is 0.00875 wt %; the content of diethylenetriamine is 0.00125 wt %, and a UV adhesive composition is obtained.
[0158] Embodiment 28
[0159] The difference between Example 28 and Example 1 is that the content of toluene diisocyanate is 0.307 wt %, and the content of diethylenetriamine is 0.003 wt %, to obtain a viscose composition.
[0160] Embodiment 29
[0161] The difference between Example 29 and Example 1 is that the content of toluene diisocyanate is 0.221 wt %, and the content of diethylenetriamine is 0.089 wt %, to obtain a viscose composition.
[0162] Embodiment 30
[0163] The difference between Example 30 and Example 1 is that the content of toluene diisocyanate is 0.207 wt %, and the content of diethylenetriamine is 0.103 wt %, to obtain a viscose composition.
[0164] The UV adhesive compositions of Examples 31 to 33 correspond to Tables 3 to 5 respectively.
[0165] Table 3
[0166]
[0167] Table 4
[0168]
[0169]
[0170] Table 5
[0171]
[0172]
[0173] The UV adhesive compositions of Comparative Examples 1 and 2 correspond to Table 6 and Table 7 respectively.
[0174] Table 6
[0175]
[0176] Table 7
[0177]
[0178]
[0179] Comparative Example 3
[0180] The difference between Comparative Example 3 and Example 1 is that the content of resin A1 is 40 wt %, and the contents of resin A2, resin A3, resin B1 and resin B2 are all 0 wt %, to obtain a UV adhesive composition.
[0181] Comparative Example 4
[0182] The difference between Comparative Example 4 and Example 1 is that the contents of resin A1, resin A2 and resin A3 are all 0 wt %, the content of resin B1 is 20 wt %, and the content of resin B2 is 20 wt %, to obtain a UV adhesive composition.
[0183] Comparative Example 5
[0184] The difference between Comparative Example 5 and Example 1 is that
[0185] The content of resin A1 is 15wt%, the content of resin B1 is 7.5wt%, and the content of resin B2 is 7.5wt%;
[0186] The content of methyl methacrylate is 8wt%, the content of dipropylene glycol diacrylate is 2wt%, the content of ethoxylated bisphenol A epoxy acrylate is 20wt%, and the content of diepoxy ethylene glycol bisglycidyl ether is 30wt%;
[0187] The content of butyl acetate is 2wt%;
[0188] The content of lithium bis(trifluoromethanesulfonyl)imide LiTFSI is 3wt%;
[0189] The content of benzil dimethyl ether (651) is 3 wt%;
[0190] The content of toluene diisocyanate is 1.9 wt %; the content of diethylenetriamine is 0.1 wt %, and a UV adhesive composition is obtained.
[0191] Prepare UV anti-viscosity film according to the following method:
[0192] The mixed resin, active monomer, antistatic agent and solvent were added into a reaction kettle and mechanically stirred at a constant speed for 2 hours to obtain the main agent A.
[0193] Under yellow light or in dark, add photoinitiator to main agent A in proportion and stir mechanically for 30 minutes, then add curing agent and stir mechanically for 30 minutes to obtain antistatic UV anti-viscosity adhesive, wherein the addition ratio of each component refers to the corresponding ratio in the adhesive composition of Examples 1 to 33 and Comparative Examples 1 to 5; finally, use a coating machine to scrape or a slit coating machine to coat on 50 μm thick PET, PO and PVC substrates, etc., and put it into a 100°C oven for baking for 3 minutes after coating. After drying, the thickness of the adhesive film is about 20 μm, and then use a flat film laminating machine to attach a release film, select the release surface of the PET light release film and attach it to the dried UV anti-viscosity adhesive, and finally obtain a UV anti-viscosity film.
[0194] Peel strength test:
[0195] The UV anti-adhesion films prepared above were cut into 25 mm wide and 150 mm long, and the release films were removed and attached to stainless steel plates (SUS), PET and glass substrates respectively. They were pressed 6 times with a 2kg roller respectively. At room temperature, the pre-UV peel strength was tested with Instron 34SC1. The post-UV peel strength was tested with Tobo 8203S after standing under yellow light for 20 minutes.
[0196] Reliability test:
[0197] The UV anti-adhesion films prepared above were cut into 25 mm wide and 150 mm long, and the release films were removed and attached to stainless steel plates (SUS), PET and glass substrates respectively. They were pressed 6 times with a 2kg roller, and the pre-UV peel strength was tested with Instron 34SC1 at 85°C and RH85%. The post-UV peel strength was tested with Tobo 8203S after standing under yellow light for 240 hours in the same way.
[0198] Resistance test:
[0199] The surface resistance was measured using a SIMCO ST-4 surface resistance meter.
[0200] The test requirements for peel strength at room temperature, the test requirements at 85°C and RH85% (standing for 240 hours), and the test requirements for resistance are shown in Table 8. The test results for peel strength at room temperature are listed in Table 9, and the test results at 85°C and RH85% (standing for 240 hours) are listed in Table 10.
[0201] Table 8
[0202]
[0203] Table 9
[0204]
[0205]
[0206] Table 10
[0207]
[0208]
[0209]
[0210] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0211] The present application achieves the appropriate viscosity of the adherend through the mutual cooperation of non-photosensitive resin and photosensitive resin, through heat curing and light curing. When UV irradiation with appropriate energy is provided, the photoinitiator absorbs the radiation energy, and after chemical changes, produces free radicals with initiator polymerization ability, which then cross-link and cure with the photosensitive resin, causing the UV glue to lose its bonding ability, that is, achieving the effect of reducing viscosity. The UV viscosity-reducing glue obtained by the cooperation with the other components has an appropriate cross-linking density, hardness and viscosity, which helps to reduce the probability of glue overflow, reduce the difficulty of peeling in the process, and improve the process yield.
[0212] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A UV adhesive composition, characterized in that: In terms of mass percentage, the UV adhesive composition comprises: 38-80wt% of mixed resin; 10-48 wt% of active monomer; 0.01-5wt% of photoinitiator; 0.01-5wt% of a curing agent; 0.01-40 wt % of solvent; Wherein, the mixed resin is a non-photosensitive resin and a photosensitive resin, the non-photosensitive resin is selected from any one or more of epoxy resin, hydroxyl-containing resin, and polyurethane resin, and the photosensitive resin is a bifunctional acrylic resin and / or a multifunctional acrylic resin; The mass ratio of the epoxy resin, the hydroxyl-containing resin and the polyurethane resin is 1:0.4-4:0.4-4.
2. The UV adhesive composition according to claim 1, characterized in that: The content of the non-photosensitive resin is 35-50 wt %.
3. The UV adhesive composition according to claim 1, characterized in that: The mass ratio of the non-photosensitive resin to the photosensitive resin is 0.8-1.6:
1.
4. The UV adhesive composition according to claim 1 or 2, characterized in that: The weight average molecular weight Mw of the epoxy resin is 5000 to 60000; and / or the weight average molecular weight Mw of the hydroxyl-containing resin is 3000 to 60000; And / or the weight average molecular weight Mw of the polyurethane resin is 5,000 to 100,000.
5. The UV adhesive composition according to claim 1 or 2, characterized in that: The epoxy resin is selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, and bisphenol F epoxy resin.
6. The UV adhesive composition according to claim 1 or 2, characterized in that: The hydroxyl-containing resin is selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, and diepoxy ethylene glycol bisglycidyl ether resin.
7. The UV adhesive composition according to claim 1 or 2, characterized in that: The polyurethane resin is selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin and polyester polyurethane resin.
8. The UV adhesive composition according to claim 1 or 2, characterized in that: The weight average molecular weight Mw of the photosensitive resin is 3,000 to 100,000.
9. The UV adhesive composition according to claim 8, characterized in that: The weight average molecular weight Mw of the photosensitive resin is 5,000 to 50,000.
10. The UV adhesive composition according to claim 1 or 2, characterized in that: The bifunctional acrylic resin is selected from any one or more of bisphenol A epoxy acrylic resin, polyurethane acrylic resin, and polyester acrylic resin.
11. The UV adhesive composition according to claim 1 or 2, characterized in that: The content of the bifunctional acrylic resin is 10-40 wt %.
12. The UV adhesive composition according to claim 1 or 2, characterized in that: The multifunctional acrylic resin is selected from any one or more of graft-modified acrylic resin, phenolic epoxy acrylic resin, and polyurethane acrylic resin. The graft-modified acrylic resin is an acrylic resin with a (meth) acrylic monomer grafted on the side chain.
13. The UV adhesive composition according to claim 12, characterized in that: The (meth)acrylic monomer is selected from any one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl acrylate.
14. The UV adhesive composition according to claim 1 or 2, characterized in that: The content of the multifunctional acrylic resin is 10-30 wt %.
15. The UV adhesive composition according to claim 1 or 2, characterized in that: The mass ratio of the bifunctional acrylic resin to the multifunctional acrylic resin is 1 to 4:
1.
16. The UV adhesive composition according to claim 1 or 2, characterized in that: The mass ratio of the mixed resin to the active monomer is 1:0.5-4.
17. The UV adhesive composition according to claim 1 or 2, characterized in that: The active monomer is a photosensitive monomer and / or a non-photosensitive monomer. The content of the photosensitive monomer is ≤40wt%, and the content of the non-photosensitive monomer is ≥30wt%.
18. The UV adhesive composition according to claim 17, characterized in that: The photosensitive monomer includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer, the mass of the difunctional monomer and / or the multifunctional monomer is denoted as m, and the ratio of the mass of the monofunctional monomer to m is 1:1-5.
19. The UV adhesive composition according to claim 17, characterized in that: The non-photosensitive monomer includes any one or more of a monomer containing a hydroxyl group and a monomer containing an epoxy group.
20. The UV adhesive composition according to claim 1, characterized in that: The content of the photoinitiator is 0.05-3 wt %.
21. The UV adhesive composition according to claim 1, characterized in that: The photoinitiator is a free radical photoinitiator.
22. The UV adhesive composition according to claim 21, characterized in that: The free radical photoinitiator is selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
23. The UV adhesive composition according to claim 1, characterized in that: The content of the curing agent is 0.5-2wt%.
24. The UV adhesive composition according to claim 1, characterized in that: The curing agent includes an isocyanate curing agent.
25. The UV adhesive composition according to claim 24, characterized in that: The isocyanate curing agent is selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate.
26. The UV adhesive composition according to claim 24, characterized in that: The curing agent also includes an amine curing agent.
27. The UV adhesive composition according to claim 26, characterized in that: The mass ratio of the isocyanate curing agent to the amine curing agent is 1:0.01-0.
4.
28. The UV adhesive composition according to claim 26, characterized in that: The amine curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine and polyethylenepolyamine.
29. The UV adhesive composition according to claim 1, characterized in that: The UV adhesive composition further comprises 0.01 to 5 wt % of an antistatic agent.
30. The UV adhesive composition according to claim 29, characterized in that: The UV adhesive composition further comprises 0.05-3 wt % of an antistatic agent.
31. The UV adhesive composition according to claim 29, characterized in that: The antistatic agent is selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonyl imide), tributylmethylammonium bis(trifluoromethanesulfonyl imide salt, and nanometal wires.
32. The UV adhesive composition according to claim 1, characterized in that: The content of the solvent is 10-30 wt %.
33. The UV adhesive composition according to claim 1, characterized in that: The solvent is selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether and toluene.
34. A UV viscosity-reducing adhesive, prepared by mixing the components of an adhesive composition, characterized in that: The adhesive composition is the UV adhesive composition according to any one of claims 1 to 33.
35. A UV anti-viscosity film, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, characterized in that: The UV viscosity-reducing adhesive is the UV viscosity-reducing adhesive described in claim 34.
Citation Information
Patent Citations
High temperature resistant UV adhesion-reducing adhesive and preparation method of protective film
CN110408351A
Cited By
Self-initiation type migration-free UV viscosity-reducing adhesive and preparation method thereof
CN121343513A